Oil price benchmarks in international trade: the Dubai benchmark and its role in the international oil pricing system - Fattouh, B (Oxford Institute for Energy Studies, 2012)
Dubai became the main price marker for the Gulf region by default in the mid 1980s, when it was one of the few Gulf crudes available for sale on the spot market. Also, until very recently, Dubai allowed oil companies to own equity in Dubai production – unlike other countries in the Gulf such as Iran, Kuwait, and Saudi Arabia. When the Dubai market first emerged, few trading companies participated in it, with little volume of trading taking place. This, however, changed during the period 1985–87 when many Japanese trading houses and Wall Street refiners started entering the market. But the major impetus came in 1988 when key OPEC countries abandoned the administered pricing system and started pricing their crude export to Asia on the basis of Dubai crude. Over a short period of time, Dubai became responsible for pricing millions of barrels on a daily basis, and the Dubai market became known as the ‘Brent of the East’. Despite the existence of other regional crudes with a much larger physical base, more than 25 years have now passed, and most cargoes from the Gulf destined for Asia are still priced against Dubai or Oman or a combination of these crudes. Nevertheless, the nature of the Dubai benchmark has evolved and many of the institutional and pricing details have witnessed major transformations, driven in large part by the decline in Dubai’s oil production and innovations in the pricing mechanisms introduced in the 2000s. Perhaps what remains from the 1980s pricing system is just the brand name ‘Dubai’.